Soil Bacterial and Viral Dynamics - Adams, Edward Stephen (2006)
Viruses have been shown to be responsible for considerable bacterial mortality and nutrient cycling in aquatic systems. As yet no detailed studies have been published on the role of viruses in natural soil bacterial communities despite common knowledge that viruses exist in the soil. This thesis sought to address some key questions on the ecology of soil bacterial viruses and their hosts. Disturbance through soil desiccation, nutrient inputs, rhizosphere effects and protozoan predation pressure were investigated. The first study of lysogeny in natural soil systems was also undertaken. The work presented here utilised tools and techniques commonplace in aquatic systems research and applied them to soil. A novel protocol was developed based on physical extraction of bacteria and viruses from soil and direct counting with epifluorescence microscopy. Physical extraction was achieved using shaking, ultrasound sonication and low speed centrifugation. The fluorochrome SYBR Gold was used to stain nucleic acid of extracted bacteria and viruses, and image analysis software used to determine bacterial cell volumes. Bacterial and viral abundances were in the region of 107-109 per gram of soil over a range of soil types. Significant fluctuations in viral and bacterial abundances were recorded at timescales of less than 24 h. Glucose and nitrogen addition led to substantial increases in bacterial and viral abundance. Loss of soil moisture resulted in peaks of viral abundance in sandy soils but not in a clay soil. A six-week microcosm study demonstrated that phage were not a significant regulator of bacterial abundance. Low levels of lysogeny were recorded over a range of soils when measured explicitly with Mitomycin C. The implication from that study was that viruses in soil behave differently to those in aquatic systems. Bacterial and viral abundances were highly coupled in most instances, irrespective of the potential activity of bacteria. Further fundamental studies are recommended.